2016
DOI: 10.1038/srep19026
|View full text |Cite
|
Sign up to set email alerts
|

The Neurochemical and Microstructural Changes in the Brain of Systemic Lupus Erythematosus Patients: A Multimodal MRI Study

Abstract: The diagnosis and pathology of neuropsychiatric systemic lupus erythematosus (NPSLE) remains challenging. Herein, we used multimodal imaging to assess anatomical and functional changes in brains of SLE patients instead of a single MRI approach generally used in previous studies. Twenty-two NPSLE patients, 21 non-NPSLE patients and 20 healthy controls (HCs) underwent 3.0 T MRI with multivoxel magnetic resonance spectroscopy, T1-weighted volumetric images for voxel based morphometry (VBM) and diffusional kurtosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 53 publications
0
49
0
3
Order By: Relevance
“…The finding could suggest that the vmPFC, as part of an executive control network, could be involved in the pathogenesis of SLE. The increase of SLEDAI is associated with decreased regional 18FDG uptakes in the gray matter volume, which may have a significant impact of lowering SLE disease activity early on, due to the enhancement of executive functioning . Hou et al found that disease activity positively correlated with functional connectivity strength in the frontal‐parietal cortex in SLE patients compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding could suggest that the vmPFC, as part of an executive control network, could be involved in the pathogenesis of SLE. The increase of SLEDAI is associated with decreased regional 18FDG uptakes in the gray matter volume, which may have a significant impact of lowering SLE disease activity early on, due to the enhancement of executive functioning . Hou et al found that disease activity positively correlated with functional connectivity strength in the frontal‐parietal cortex in SLE patients compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of SLE-DAI is associated with decreased regional 18FDG uptakes in the gray matter volume, which may have a significant impact of lowering SLE disease activity early on, due to the enhancement of executive functioning. 38 Hou et al found that disease activity positively correlated with functional connectivity strength in the frontal-parietal cortex in SLE patients compared with healthy controls. They have also shown that the relatively decreased activity in SLE patients might be transient, and it is probably dependent on disease activity, as the activity will increase after treatment and changes in patients progressing from active to inactive disease.…”
Section: Relationship Between Limbic System Dysfunction and Depressiomentioning
confidence: 99%
“…Lower NAA and higher Cho and MI levels have been reported in SLE and NP-SLE patients when compared to healthy controls, suggesting decreased neuronal function and glial activation, respectively (73, 80, 8790). More recently, lower NAA changes in NP-SLE patients when compared with SLE and in SLE with high disease activity when compared with low activity were found (91, 92). Diffusion weighted MRS (DWS) probes the mobility of intracellular metabolites in the cytoplasm, and is thus able to detect cytomorphological changes in disease (93).…”
Section: The Challenges Of Establishing a Neuroimaging Biomarker In Nmentioning
confidence: 99%
“…LPS-induced CPI resulted in grey matter loss in several brain regions, which was in line with the previous human MRI studies revealing grey matter loss in the Hippcampus, Thal, Hypo-Thal, amygdala, insula, Cg, CPu, VC, occipitotemporal area and sensorimotor cortex (von Leupoldt et al, 2011;Zhang et al, 2013, Chen et al, 2016 in patients with sustained pulmonary inflammation, such as chronic obstructive pulmonary disease (COPD) and asthma. Similar regions, such as the CPu, Cg, Thal, occipitotemporal area and motor cortex were reported to be affected in some chronic infectious diseases (Zikou et al, 2014;Hjerrild et al, 2016) and in patients with inflammatory autoimmune diseases, such as rheumatoid arthritis (Wartolowska et al, 2012) and systemic lupus erythematosus (Zhang et al, 2016b). Among these brain regions, hippcampus, SN, CPu, Cg, and insula have been associated with abnormally enhanced levels of pro-inflammatory cytokines (IL-6, IL-1β, TNF-α) in previous human fMRI studies (brain functional changes in response to acutely stimulated peripheral infection) (Brydon et al, 2008;Harrison et al, 2009).…”
Section: Mri Findingsmentioning
confidence: 78%